Social security programs and retirement around the world reforms and retirement incentives - Börsch-Supan, Axel, 1954-; Coile, Courtney (National Bureau of Economic Research conference report., 2020)
"This ninth volume of the International Social Security series, which studies the social security and retirement experiences of 12 developed countries, examines the effects of pension reform on employment at older ages. In the two decades since the project began, a dramatic decline in men's labor force participation has been replaced by sharply rising participation rates. Older women's participation has increased dramatically as well. While better health, more education, and changes in labor supply behavior of married couples may have affected this trend, these factors alone cannot explain the magnitude of the employment increase and its large variation across countries. Concurrently with rising participation rates, countries have undertaken numerous reforms of their social security programs, disability programs, and other public benefit programs for older workers. Using a common template for analysis across the 12 countries so that results are easily compared, the studies in this volume explore how financial incentives to work at older ages have evolved from 1980 to the present as a result of public pension reforms, and how much of the changes in employment over this period can be explained by these changing incentives. Overall, the findings support the hypothesis that social security reforms have strengthened the incentives for work at older ages, and that these enhanced financial incentives contributed to the rise in employment at older ages during this period"--